PERAN BRAND AWARENESS DALAM MEMEDIASI PENGARUH DAYA TARIK IKLAN TERHADAP NIAT BELI - Paramita Dewi, Dewa Ayu Diah; Jatra, I Made (E-Jurnal Manajemen, 2018)
This study aims to determine the effect of advertising attractiveness and brand awareness on buying intentions, as well as the role of brand awareness in mediating the effect of advertising attractiveness on purchasing intentions, a study conducted on Vivo brand smartphone products in Denpasar City. This research was conducted in Denpasar City by using sample size amounted to 100 people, through purposive sampling method. Data collection was done by distributing questionnaires measured by 12 indicators and using Likert scale. The analytical technique used in this study is path analysis and accompanied by a sobel test. The results of this study showed that the attractiveness of advertising has a positive and significant impact on brand awareness. The attractiveness of advertising has a positive and significant impact on purchasing intentions, brand awareness has a positive and significant impact on purchasing intentions. This study also proves that brand awareness is able to mediate the relationship between the effects of advertising attractiveness on buying intentions. Keywords : Ad Attractiveness, Brand Awareness, Purchase Interest